Learning Management of UNP’s Students and its Implication to Guidance and Counseling - Adnan Arafani; Asmidir Ilyas; Zikra Zikra (International Conferences on Educational, Social Sciences and Technology)
Learning management is process and activities to manage the learning efforts and to keep the achievable of goals. Leaning management is also associated with interaction in the learning process with other human beings as well as with learning environment, learning outcomes and the objectives. This research is based on the problems that cause the delay of completing the study of organizational activists among students. The research method is quantitative with descriptive approach. Research subjects involved in this study were as many as 73 people. The instrument used is a questionnaire. From the results of the study noted that the overall ability of student learning management among student activists is in the category of “capable”. This result study recommends campus’s leader to help the sustainability of “good“ learning management, counseling lecturers and UPBK (campus’s counseling center) should provide appropriate services in maintaining good learning management and improve management skills for students who are still “less able” to manage their learning.